“Unite the foods” - playing with food through classroom experience (Research, Society and Development, 2021)
Objective: To describe the experience, developed through active methodology in the classroom, of creating a game as a method of teaching about healthy eating for children aged six to eleven years old through playfulness. Methodology: This article is a descriptive, reflective experience report, created as a proposal of the discipline of Integral Assistance to Child and Adolescent Health I of the undergraduate course in Nursing at the Federal University of Uberlândia, from May to June 2019. The game was applied in class with 30 undergraduate nursing students, subdivided into 3 groups of 10 people. To conduct the game, the authors of the paper distributed themselves in the smaller groups as moderators, so it was possible to observe the interaction of the participants of the activities. Discussion: The game was planned based on the previous knowledge of the child and the starting point of their development and sought to explore in a playful way the social-cognitive sphere. For the students, it allowed them to experience the difficulties in developing teaching resources and at the same time highlighted the importance of play in teaching children. Final considerations: The proposed activity was fundamental to provide reflections on how important playful activities are for children's learning. The nurse has the role of an educator, and through games should help children to take care of themselves and promote health.